Effects of selected tricyclic antidepressants on early-life stages of common carp (Cyprinus carpio). (October 2017) - Sehonova, Pavla; Plhalova, Lucie; Blahova, Jana; Doubkova, Veronika; Marsalek, Petr; Prokes, Miroslav; Tichy, Frantisek; Skladana, Michaela; Fiorino, Emma; Mikula, Premysl; Vecerek, Vladimir; Faggio, Caterina; et al.
Abstract: Despite the fact that pharmaceuticals occur in surface water in low concentrations, they can still have adverse effect on aquatic biota, because these substances are designed to have a specific mode of action even at low concentrations. To our knowledge, only little is known about the long-term effect of tricyclic antidepressant residues on non-target animals, especially fish. Hence, the aim of this study was to assess the effect of subchronic exposure to selected tricyclic antidepressants – namely, amitriptyline, nortriptyline, and clomipramine and their mixture – on early-life stages of common carp (Cyprinus carpio) . Two embryo-larval toxicity tests with common carp were performed, each taking 30 days. For the experiment, three tricyclic antidepressants as well as their mixtures were tested at three different concentrations – 10, 100 and 500 μg/L. Hatching and mortality were recorded twice a day. In addition, samples were taken at regular intervals in order to record developmental stage, morphometric and condition characteristics and morphological anomalies. At the end of the test, additional samples were taken for histopathological examination and also for the determination of antioxidant and biotransformation enzyme activity and lipid peroxidation and protein carbonylation. Long-term exposure resulted in a significant increase in mortality, developmental retardation, morphological anomalies, and pathological changes in brain, heart, and cranial and caudal kidney. In addition, changes in antioxidant enzyme activity as well as increased lipid peroxidation were observed, even at the lowest tested concentrations. Hence, environmentally relevant concentrations of TCAs have the potential to cause harmful effects on early-life stages of fish. Highlights: Significant changes in mortality were observed. Damage of heart, brain and kidney was revealed. The exposure resulted in oxidative damage of lipids.